Antioxidant Activity and Nanoemulsion Formulation of Chlorella vulgaris Ethanolic Extract for Potential Topical Applications - Eskarani Tri Pratiwi; Windah Anugrah Subaidah; Neneng Rachmalia Izzatul Mukhlishah; Baiq Dwiyan Nugrahani; Muhammad Dimas Arzy (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Chlorella vulgaris is a marine microalga abundant in West Nusa Tenggara (NTB) that contains flavonoids and other bioactive compounds exhibiting potent antioxidant activity. Antioxidant compounds can be utilized in skin maintenance. This research investigated the antioxidant activity of C. vulgaris ethanolic extract while developing a nanoemulsion formulation intended for topical application. Biomass was processed into simplisia and extracted by maceration using ethanol 96%. Phytochemical identification and total flavonoid content were determined using TLC and aluminum chloride methods. Antioxidant activity was determined using the DPPH radical scavenging assay and expressed as IC₅₀ values. The extract was subsequently formulated into nanoemulsions using virgin coconut oil, Tween 80, and Span 80, followed by physical characterization. The extraction process produced a C. vulgaris extract yield of 7.14% (w/w). TLC analysis confirmed the presence of flavonoids, and the TFC of the extract was 89,31 ± 0,03 mg QE/g extract. Strong antioxidant activity was demonstrated by the ethanolic extract, with an IC₅₀ of 52.869 ppm. The nanoemulsion formulation containing 1% extract exhibited a green color, characteristic odor, clear appearance, with a pH value of 6,96, viscosity of 990 cPs, a transmittance value of 89,8%, particle size of 16,5 nm, and polydispersity index 0,294, indicating the formation of a nanosized dispersion with moderate particle size distribution. Overall, Nanoemulsion delivery enhances C. vulgaris antioxidant performance, supporting its potential application in skin maintenance and cosmeceutical products.